2017
DOI: 10.1103/physrevlett.119.044802
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Control of Plasma Wakefields by Multiple Laser Pulses

Abstract: We demonstrate experimentally the resonant excitation of plasma waves by trains of laser pulses. We also take an important first step to achieving an energy recovery plasma accelerator by showing that unused wakefield energy can be removed by an out-of-resonance trailing laser pulse. The measured laser wakefields are found to be in excellent agreement with analytical and numerical models of wakefield excitation in the linear regime. Our results indicate a promising direction for achieving highly controlled, Ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Very recently J. Cowley et al [40] reported on very encouraging results about the feasibility of their timeshaping setup, with the demonstration of efficient exci-tation of the plasma wave via Multi-Pulse LWFA. The REMPI scheme could be tested with two pulses in the train at first, with Nitrogen as a contaminant species.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently J. Cowley et al [40] reported on very encouraging results about the feasibility of their timeshaping setup, with the demonstration of efficient exci-tation of the plasma wave via Multi-Pulse LWFA. The REMPI scheme could be tested with two pulses in the train at first, with Nitrogen as a contaminant species.…”
Section: Discussionmentioning
confidence: 99%
“…Inset: the ionizing pulse focusing is achieved by using a mirror with a hole for the driving pulse passage. pulses demonstrate that a multi pulse scheme is obtainable with present day technology and that plasma waves can be excited with this scheme [7]. Using Argon (Ar 8+ → Ar 9+ with ionization potential U I = 422.5 eV ) as a dopant gives us the possibility to obtain bunches with tens of nmĂ—rad of normalized emittance.…”
Section: The Resonant Multi-pulse Ionization Injectionmentioning
confidence: 94%
“…To this purpose, a small fraction of the laser pulse is picked up and frequency doubled or tripled by a nonlinear crystal, while the most energetic fraction (almost 97% of the total energy, in the case being studied for EuPRAXIA) is shaped temporally as a sequence of sub-pulses. Over the past few years, a few optical schemes were proposed in order to produce a train of ultrashort pulses from a CPA TiSa chain [8][9][10]. However, in their proposed variants these schemes do not meet the two essential requisites for driving the ReMPI acceleration scheme within EuPRAXIA, namely a high efficiency (energy throughput into the pulse train) and reduced amplitude variations among the different pulses of the train.…”
Section: Options For Pulse Train Generationmentioning
confidence: 99%